Le bois d'œuvre et le port de Montréal, 1830-1870: une approche dendroarchéologique - Poudret-Barré, Alexandre (Université de Montréal, 2007)
Keywords: Port

Muddy Shore to Modern Port: Redimensioning the Montréal Waterfront Time-Space - Gilliland, Jason A. (The Canadian Geographer / Le Géographe canadien, 2004)
Number: 4
Keywords: Paysages; Port

The Engineers' Engineer: Sir John Kennedy and the Port of Montreal - White, Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Ingénieurs; Port

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Intermodal Freight Terminals: Locality and Industrial Linkages - McCalla, Robert J.; Slack, Brian; Comtois, Claude (The Canadian Geographer / Le Géographe canadien, 2001)
Number: 3
Keywords: Aéroport; Chemins de fer; Port

94 ans après la Conquête un premier navire français à Montréal - Gaudet, Sylvain (Montréal en tête, 2006)
issued: 2006-24-00
Keywords: Commerce de détail; Marchands; Port

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Number: 2
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Le commerce de l'infortune. Les premiers régimes d'assurance maladie au Québec, 1880-1939 - Rousseau, Yvan (Revue d'histoire de l'Amérique française, 2004)
Si le lancement des plans d’assurance hospitalisation de la Croix Bleue en 1942 apparaît indubitablement comme un tournant dans le développement du marché de la protection contre la maladie, des expériences avaient longuement préparé le terrain. Cet article retrace les grandes étapes de la mise en place des régimes d’assurance maladie privés au Québec, depuis la fin du XIXe siècle jusqu’à la Seconde Guerre mondiale. Il est l’occasion d’examiner trois grands contextes : 1) le développement des régimes d’indemnisation fondés sur l’allocation de prestations en espèces (ceux des entreprises commerciales comme des sociétés fraternelles) ; 2) la crise des régimes d’assurance volontaire dans l’entre-deux-guerres ; 3) les efforts déployés par les promoteurs de l’assurance libérale pour mettre au point des formules de prépaiement à l’égard des frais hospitaliers et médicaux. Dans le cadre de débats mouvementés autour de l’accès aux soins de santé, un grand défi doit alors être relevé : ouvrir les portes de l’hôpital à ceux qu’on désigne à l’époque sous le vocable de « classe moyenne ».
issued: 2004-23-00
Keywords: Assurance

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."–BOOK JACKET.
Keywords: Navigation